'"Wherever I can work, I've got to go": negotiating mobilities in the context of volatility in the Canadian construction industry'. (1st October 2020) - Barber, Lachlan; Breslin, Samantha
ABSTRACT: This article considers how construction workers based in the Canadian province of Newfoundland and Labrador (NL) negotiate the need to be mobile for work at different scales and with what effects. It tackles the seldom considered question of how travel becomes normalized as a facet of work in construction, an employment sector characterized by volatility. Specifically, we explore the experiences of workers and their families negotiating the shift from having extensive employment options in different places during a time of high labour demand, to limited and constrained options that may require significant changes (for instance, relocation, more time apart from family, or lower pay) in a period of economic contraction. How workers respond to these conditions contributes to conceptualizations of agency and mobility in construction workplace cultures. The article draws on 73 semi-structured interviews with workers, employers and industry and community stakeholders conducted between 2014 and 2018, and data from project employment reports and field observations. The article reveals how long commutes and extended periods away from home are understood to be inevitable aspects of construction work that shape the field of expectations of workers and their families, and what this dominant discourse means on the ground in lived experience.